THE RELATIONSHIP BETWEEN THE DEMONSTRATION AND THE INTERESTS OF FIQIH LEARNING METHOD WITH STUDENTS FIQIH LEARNING ACHIEVEMENT - Saepudin, Saepudin (Tawazun: Jurnal Pendidikan Islam, 2018)
The objective of this research is to study the relationship between demonstration method and learning interest with fiqih learning achievement, individually as well as together. The hypothesis to examined are (1) there are positive relationship between demonstration method with fiqih learning achievement, (2) there are positive relationship learning interest with fiqih learning achievement, and (3) there are positive relationship between demonstration method and learning interest with fiqih learning achievemen. The research was conducted at Junior Midle School al-Kamal Jakarta. The research method was survey. The population are 113 student, the sample was 70 student, using simple of random sampling technique. The instrument was questioner of demonstration method, learning interest, and fiqih learning achievement. The instruments were validated with product moment for demonstration method and learning. Then, reliability with al-pha cronbach for demonstration method and attitude towards fiqih learning. The instrument was questioner of fiqih learning achievement were validated with Point Biserial. Then, reliability with Kuder Ricdhadson (KR-20) for questioner of fiqih learning achievement. Data are analyzed using with regression and correlation technique (Simple and Multiple). The research concluded that fiqih learning achievement might increase the demonstration method and learning interest. Keywords : Demonstration Method, Learning Interest, Fiqih Learning Achievement